Kosmiese wet, noodsaaklikheid en waarskynlikheid: Armstrong se beskouing op natuur- en waarskynlikheidswette en Van Fraassen se kritiek daarop (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2024)
In this article, an outline is mainly given of Armstrong’s view of natural laws and probability laws and of Van Fraassen’s criticism thereof. Armstrong considers natural laws as necessary relations between universals and attempts to relate the problem of probability laws to his theory of universals as well. Van Fraassen claims that Armstrong’s view runs up against what he calls the identification and inference problem. The identification problem asks back to what is the law-generating (law-making) relationship that applies between universals and the conclusion problem asks what information the statement that one property is in relation to another property offers us about events and how things are. An important problem that also arises from this debate is Armstrong’s view of natural laws and the regression problem. The important underlying problem here is the ‘reification’ of universals, even if Armstrong does not consider universals to be ‘substances’. It will also become clear that issues such as necessity, causality and probability are at issue in Armstrong’s exposition of what laws of nature and probability are. A further conclusion that this article tries to draw is that law and reality are an irreducible given that Armstrong and Van Fraassen must take into account. The second article will try to address the problems arising from the first article from a Christian perspective.